2011
DOI: 10.1002/clen.201000065
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation of the Precipitation Chemistry in the Thrace Region of Turkey

Abstract: Pollutants affect not only the environment in which they originate since they are also transported by air currents to other locations. For this reason, air pollution is a global problem for all countries and the air and water quality need to be monitored carefully. More information on precipitation chemistry is required to determine the source of pollution as well as its effects on the ecosystems. In this study, precipitation chemistry has been analyzed for the first time by using simple bulk collectors locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…To date, many studies around the world have revealed the source types, formation mechanisms, chemical and physical characteristics, and dry and wet deposition of the major water-soluble inorganic ions. 2,[6][7][8][9][10] The rapid economic growth in China during the past three decades has caused many environmental pollution problems. For example, one third of the Chinese territory has been affected by acid rain, with some megacities in southern China experiencing rain with an annual mean pH as low as 3.…”
Section: Environmental Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many studies around the world have revealed the source types, formation mechanisms, chemical and physical characteristics, and dry and wet deposition of the major water-soluble inorganic ions. 2,[6][7][8][9][10] The rapid economic growth in China during the past three decades has caused many environmental pollution problems. For example, one third of the Chinese territory has been affected by acid rain, with some megacities in southern China experiencing rain with an annual mean pH as low as 3.…”
Section: Environmental Impactmentioning
confidence: 99%
“…Air mass backtrajectory is another useful tool to identify the possible sources and transport pathways of air pollution and precipitation. 2,9 In this study, a 48 h air mass back-trajectory was generated using the NOAA HYSPLIT 4 trajectory model to help analyze the sources of ionic species in the collected precipitation samples. Precipitation events from the air masses of the same directions will be defined as the same trajectory cluster.…”
Section: 24mentioning
confidence: 99%